Thirty-three-year-old textiloma found during exploratory laparotomy: a case report - Velázquez, José Miguel Huerta; Gómez, Carlos Octavio García (International Surgery Journal, 2022)
The problem caused by a retained surgical sponge is known as a textiloma. Surgical gauze pads can be easily retained due to their ubiquitous use, their relatively small size, and when soaked in blood, making them difficult to distinguish from surrounding tissues. In most cases, the diagnosis of a textiloma is usually given in the following days of a surgical intervention, but there are few cases reported in the literature where a textiloma persists for a variable number of years. A 63-year-old female with a surgical history of a caesarean section 33 year ago complaining of an abdominal palpable mass and chronic abdominal pain. CT scan findings suggested the diagnosis of textiloma, the exploratory laparotomy revealed an encapsulated mass which was completely excised, and intraoperative study confirmed the diagnosis of textiloma. Textilomas occur infrequently and can be a source of great concern to the surgeon and the patient. Foreign bodies within body cavities and organs can present with several nonspecific clinical features that can make diagnosis difficult. An aseptic fibrotic reaction causes that the textilomas can remain asymptomatic for many years, with very few cases of 30 or more years old textilomas reported in the literature. Surgical removal remains as the treatment of choice. Textiloma can be a life-threatening problem that is an avoidable complication. Textilomas should be part of the differential diagnosis of abdominal tumors even after a 30-year surgical history.